PENERAPAN GOOGLE CLASS ROOM DAN GOOGLE MEET DALAM PEMBELAJARAN PEMESANAN PENGHITUNGAN TARIF PENERBANGAN DI KELAS XI USAHA PERJALANAN WISATA SMK NEGERI 1 KOTA TERNATE - Julita Mubin; Roswita M Aboe (Universitas Khairun, 2021)
Learning conditions in the Tourism Travel Business Department of SMK Negeri 1 Ternate City require an active, innovative, creative, effective, and fun learning concept. This is based on material characteristics such as Booking Flight Fare Calculation, which requires students to understand the theory as well as be able to apply it later at the implementation of street vendors and when they work in the Tourism Industry later. The purpose of this study is to increase the activeness of students and student learning outcomes through the application of google classroom and google meet. This type of research is classroom action research (Classroom Action Research). The research was carried out in collaboration between researchers, teachers and students. The research subjects are 60 students of class XI.SMK Negeri 1 Ternate City in the 2020/2021 academic year. Data collection techniques used simple observations and questionnaires. The research procedure includes the following stages: (a) planning, (b) implementation (c) observation, and (d) reflection. Based on the research results, the implementation of Google Classroom and Google Meet has an increase in the activeness of students. Where from cycle I, 33 respondent Choose agree with the use of the application, and student learning outcomes obtained was 53.4%. In cycle II the activeness of students increased to 70 percent and student learning outcomes achieved 76.7%. There was an increase from cycle I to cycle II of 23.3%. Therefore it can be concluded that this study is successfully increased students activity in the process of teaching and learning.